An Empirical Study on Lean Performance Parameters of Manufacturing Sector. Issue 1 (March 2021) - Vijayvargy, Lokesh; Gupta, Srikant
Abstract: Growth and GDP of any nation is depend on its in-house manufacturing capacity. Due to manufacturing many countries like: China, Japan, USA, and Korea are leading world in growth and employability. But due to low cost and govt. policy, India is one of the most lucrative option for manufacturing industry to prosper. This paper will help us in identification of lean performance parameters of manufacturing companies in India. Data were collected in form of questionnaire by mangers of 100 manufacturing firms to identify various lean performance parameters. Sample of manufacturing industry are like agriculture tools and equipment's, Material handling equipment's, Parts of various machines parts and construction machines and parts, bolts and nuts, etc are included in our research. The respondent has different position in organization like HR manager, operations manager, SCM manager, owner, director, etc. To identify parameters of lean performance, this study used statistical tools. The outcomes of the research work offer the important implications for the Indian manufacturing organizations to understand the factors affecting their performance.